2013
DOI: 10.1007/s00468-013-0967-9
|View full text |Cite
|
Sign up to set email alerts
|

Carbonylated proteins accumulated as vitality decreases during long-term storage of beech (Fagus sylvatica L.) seeds

Abstract: Key message Carbonylation of proteins associated with a stress response may contribute to the lowered viability of naturally aged beech seeds, especially the desiccation tolerance-associated proteins and USP-like protein.Abstract Proteins are modified by a large number of reactions that involve reactive oxygen species-mediated oxidation. The direct oxidation of amino acids produces 2,4-dinitrophenylhydrazine-detectable protein products. Carbonylation is irreversible, and carbonylated proteins are marked for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 49 publications
2
50
0
5
Order By: Relevance
“…Dry embryonic axes of beech seeds contained no more than 10 % water and thus consist of desiccated tissue. Recently, it was shown that dehydrins play a role in desiccation tolerance (Wang and others 2012), and this function is conserved in stored beech seeds (Kalemba and Pukacka 2014). Dehydrins associated with amyloplasts may act by rescuing enzyme functions in key metabolic processes during dehydration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dry embryonic axes of beech seeds contained no more than 10 % water and thus consist of desiccated tissue. Recently, it was shown that dehydrins play a role in desiccation tolerance (Wang and others 2012), and this function is conserved in stored beech seeds (Kalemba and Pukacka 2014). Dehydrins associated with amyloplasts may act by rescuing enzyme functions in key metabolic processes during dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…During development, beech seeds become desiccation tolerant beginning at the 16th week after flowering (WAF) (Kalemba and others 2009) like all other orthodox type seeds (Roberts 1973). Beech seeds were finally classified into the intermediate category (León-Lobos and Ellis 2002) due to their reduced longevity during storage (León-Lobos and Ellis 2002;Pukacka and Ratajczak 2007;Kalemba and Pukacka 2014); the seeds cannot survive dehydration below those in equilibrium with approximately 40-50 % relative humidity (Ellis and others 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The germination capacity of beech seeds stored in optimal conditions for up to 10 years was strongly positively correlated with soluble protein level, whereas a strong negative correlation was found between germination capacity and hydrogen peroxide, superoxide anion radical and lipid hydroperoxide (LHPO) levels (Pukacka and Ratajczak, 2007). A clear negative correlation was demonstrated between the protein carbonylation level and the germination capacity of beech seeds stored long-term (Kalemba and Pukacka, 2014). Ratajczak et al (2015) established that the loss of beech seed germinability is related to ROS accumulation in the root apical meristem, and DNA fragmentation occurred primarily in embryonic axes of seeds stored for 5 years or longer.…”
Section: Introductionmentioning
confidence: 92%
“…ROS prompt many oxidative injuries to macromolecular components of cells (ElMaarouf-Bouteau et al, 2011;Kranner et al, 2011), of which the most affected are proteins (Davies, 2005). Protein oxidation (i.e., carbonylation) can affect the activities of enzymes and increase the susceptibility of proteins to proteolysis (Rajjou et al, 2012;Kalemba and Pukacka, 2014). The loss of seed vigour induced by ageing is thus the result of protein changes in dry seeds during storage, the regulation of protein synthesis and turnover, and posttranslational modifications (PTMs), as well as a reduction in translational activity during germination (Rajjou et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…This modification is commonly known as a marker of oxidative metabolic disorder and in seeds it was linked mostly to process of aging and loss of viability (Terskikh et al 2008;Kalemba and Pukacka 2014) characterized by over accumulation of ROS. However, carbonylation of some proteins (e.g., proteins or peptides that serve as reserved material) is a positive process required for termination of seed germination (Job et al 2005).…”
Section: Mode Of Action Of Reactive Nitrogen Species In Seedsmentioning
confidence: 99%